The Effect of Educational Interventional Program on the Rate of Development of Ventilator Associated Pneumonia - M. Azizullah, E. M. Ahmed Qureshi, M. S. Rana, Asif Hanif, M. H. Aziz, Faisal Izhar, A. H. Asghar, M. Ashraf Zia, Nuzhat Sultana, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Ventilator Associated Pneumonia (VAP) is one of the frequent infections associated with health care in intensive care units (ICU) prolongs the hospital stay, increases care costs and mortality, and is caused by the migration of oro-pharyngeal microorganisms onto the pulmonary parenchyma. Aim: To determine the effect of educational intervention on the rate of occurrence of ventilator associated pneumonia in patients admitted in Intensive Care Unit (ICU). Place and duration of study: Study was conducted in ICU of Jinnah Hospital, a tertiary care public sector hospital in Lahore, Pakistan for a period of 12 months from August 2019 to July 2020. Study design: Interventional Study. Methods: A total of 270 Patients were enrolled in the study and were divided into two groups, (pre and post educational intervention group). Information about patient's VAP rate, its distribution and patient's length of stay in hospital collected for both groups. Results: Of total 270 enrolled patients, 115(42.6%) were males and 155 (57.4%) were females. The overall rate of VAP was observed 43(15.9%), among them 27(20%) was in pre- interventional group and 16(11.9%) in post interventional group during treatment and stay in ICU. Conclusion: It was concluded that educational intervention played a significant role in controlling the VAP among the patients admitted in the ICU. Keywords: Educational intervention, Nosocomial Infection, Ventilator Associated Pneumonia and Intensive Care Unit